A STUDY OF MICROSTRUCTUR AND MECHANICAL PROPERTIES OF CEMENT MORTAR BY ADDING NANOPARTICLES - Mohammad Reza Arefi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, research has been done on the compressive and tensile strength of cement mortar containing 1, 3 and 5 percent by weight of cements Fe2O3nano-particles. The results show that the mechanical properties of samples containing 1 and 3 percent Fe2O3nano-particles is desirable then the ordinary cement mortar. SEM study about the micro structure of cement mortar containing nano particles and ordinary cement mortar showed that Fe2O3 nano-particles fills the pores completely and reduces the mixture of CaOH2 with hydrates and increases the final density of the prepared samples. The mechanical properties results showed that by increasing iron oxide nano-particles the mechanical properties enhances to 5 percent.